The Mediating Effect of Work Engagement on the Relationship Between Work Environment and Employee Quality Service Delivery in Rural Public Health Facilities - Prosper, Protasia; Matoka, Chacha; Ngirwa, Charles Cleophace (Human Resource and Leadership Journal, 2025)
Purpose: This study investigates the mediating effect of work engagement in the relationship between the work environment and employee quality service delivery in rural public health facilities in Tanzania. It specifically examines how factors such as equipment availability, workplace safety, staff housing, workspace, and manageable workloads influence service delivery through employee engagement. Methodology: This study adopted a positivist research philosophy with a deductive approach to test hypothesized relationships. A cross-sectional survey design was employed, using self-administered structured questionnaires to collect data from 285 healthcare professionals across 63 health centers and dispensaries in the Mtwara region. Respondents were selected through multistage sampling techniques. Data were analyzed using IBM SPSS version 25 and Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. Findings: The results show that the work environment has a significant positive effect on both work engagement and employee service quality. Additionally, work engagement significantly mediates the relationship between work environment and service quality. This suggests that when healthcare workers experience better work conditions, they are more engaged and subsequently deliver higher quality services Unique Contribution to Theory, Policy and Practice: The study offers theoretical insights by applying the Job Demands-Resources (JD-R) theory, Social Exchange Theory (SET) and SERVQUAL model in a rural healthcare context. It provides practical recommendations for policymakers and health administrators to improve rural healthcare service delivery by investing in supportive work environments and engagement strategies. These findings are relevant for other underserved regions aiming to enhance public sector performance through human resource interventions.